1999
DOI: 10.1074/jbc.274.36.25330
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Bovine Hemoglobin Fragment in the Tick Boophilus microplus

Abstract: Antifungal and antibacterial activities were detected in the hemolymph and gut contents of the cattle tick, Boophilus microplus. A peptide with antibacterial activity from the tick gut contents was purified to homogeneity by reversed-phase chromatography. The molecular mass of the purified peptide was 3,205.7 Da, measured by matrix-assisted laser desorption/ionization mass spectrometry. The amino acid sequence was obtained by Edman degradation and showed that the peptide was identical to a fragment of the bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 28 publications
3
129
0
16
Order By: Relevance
“…Antimicrobial proteins and peptides have been obtained from a variety of sources such as aquatic organisms like shrimp (Cuthbertson et al, 2002), sole (Oren and Shai, 1996), flounder (Cole et al, 1997), and anchovy (Tang et al, 2015), plants (Capriotti et al, 2015), blood (Fogaca et al, 1999), milk (McCann et al, 2006), and egg (Mine et al, 2004), to name a few. One of the latest investigations to derive antimicrobial peptides from natural sources was the work performed by Capriotti et al (2015).…”
Section: Antimicrobial Effectmentioning
confidence: 99%
“…Antimicrobial proteins and peptides have been obtained from a variety of sources such as aquatic organisms like shrimp (Cuthbertson et al, 2002), sole (Oren and Shai, 1996), flounder (Cole et al, 1997), and anchovy (Tang et al, 2015), plants (Capriotti et al, 2015), blood (Fogaca et al, 1999), milk (McCann et al, 2006), and egg (Mine et al, 2004), to name a few. One of the latest investigations to derive antimicrobial peptides from natural sources was the work performed by Capriotti et al (2015).…”
Section: Antimicrobial Effectmentioning
confidence: 99%
“…Fogaca et al, [44] identified and sequenced the first antimicrobial peptides from bovine Hemoglobin (Hb). The sequence of amino acids was identified by mass spectrometry: Phe-Leu-Ser-Phe-Pro-ThrThr-Lys-Thr-Tyr-Phe-Pro-His-Phe-Asp-Leu-Ser-His-Gly-Ser-AlaGly-Val-Lys-Gly-Hys-Gly-Ala-Lys (MM 3,205.7Da) corresponding to the (f: 33-61) of α-hemoglobin.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The ACE enzyme is found in various tissues and its inhibition can influence different systems involved in the regulation of blood pressure, in addition to the immune and nervous systems [22]. ACE inhibitors have been isolated from the primary sequences of αS1-casein (fs: 23-34; 23-27; 294-299), of bovine β-casein (f: 177-183), human (f: [43][44][45][46][47][48][49][50][51][52] and of kappa-casein (f: [63][64][65]. These peptides are generally called casokinins [23].…”
Section: Antihypertensive Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Como realizam digestão intracelular, os patógenos não sofrem o ataque de enzimas digestivas no intestino dos carrapatos. Porém, já foi demonstrada a presença de peptídeos antimicrobianos (PAM) resultantes da digestão da hemoglobina do hospedeiro no intestino (Belmonte et al, 2012;Fogaça et al, 1999;Nakajima et al, 2002;Sonenshine et al, 2005). Além dos fragmentos de hemoglobina, PAM como defensinas e lisozimas também foram identificados nos intestinos de algumas espécies de carrapatos (Anderson, Magnarelli, 2008;Kopácek et al, 1999;Nakajima et al, 2002;Sonenshine et al, 2002).…”
Section: A Aquisição E a Transmissão De Riquétsias Por Carrapatosunclassified